Synthesis of size-controlled silver nanodecahedrons and their application for core–shell surface enhanced Raman scattering (SERS) tags - Lu, Haifei (2013)
We report the synthesis of silver nanodecahedrons (Ag NDs) and their use as surface enhanced Raman scattering (SERS) nano-composites. The as-prepared Ag NDs possess strong localized surface plasmon resonance (LSPR) with widely tunable peaks between 420–660 nm, which was formerly not possible, thus greatly improving the prospect of using silver nanoparticles for SERS applications. The growth of large size Ag NDs (LSPR peak longer than 490 nm) results from a seed-mediated step involving the reduction of silver cations by photo-excitation (illumination wavelength at 500 nm). Ag ND-SERS composites formed from a layer-by-layer coating technique show strong Raman signal enhancement and good material stability because of passivation effects from the coating. The reported silica-coated Ag NDs may be used with other molecular species to take advantage of field enhancement for a variety of applications, including non-linear harmonics generation and fluorescence enhancement.